The Relevance of Presidential Threshold Implementation in the 2024 Concurrent Elections - Prasasi, Cindy Ayu (Faculty of Law, Universitas Negeri Semarang, 2023)
The fortification of Indonesia's presidential system ensued through the amendment of the 1945 Constitution spanning from 1999 to 2002. This consolidation of the presidential system is exemplified by the discontinuation of the President's status as a mandatary of the People's Consultative Assembly, aligning with the nation's commitment to establish a democratic rule of law. The President, as the head of government, is now directly elected by the populace, with the inaugural direct presidential election taking place in 2004. Within this electoral process, a stipulated criterion known as the Presidential Threshold is applied. In the upcoming 2024 election, the maintenance of the presidential threshold dictates that a pair of presidential candidates proposed by a political party or an amalgamation of political parties must meet specific requirements. These include obtaining at least 20% of the total seats in the Regional Representative Council (DPR) or securing 25% of the valid votes nationally in the preceding DPR member election. While the implementation of the presidential threshold in Indonesian elections has elicited both support and criticism, proponents argue that it streamlines political parties, bolstering the presidential system and fostering government stability, particularly in the interplay between executive and legislative institutions. Conversely, detractors contend that the reliance on votes from the previous election for the application of the presidential threshold in simultaneous elections warrants reconsideration.